2021
DOI: 10.4062/biomolther.2020.081
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Synuclein Inclusion Formation in Human Oligodendrocytes

Abstract: Multiple system atrophy (MSA) is a neurodegenerative disease characterized by presence of α-synuclein-positive inclusions in the cytoplasm of oligodendrocytes. These glial cytoplasmic inclusions (GCIs) are considered an integral part of the pathogenesis of MSA, leading to demyelination and neuronal demise. What is most puzzling in the research fields of GCIs is the origin of α-synuclein aggregates in GCIs, since adult oligodendrocytes do not express high levels of α-synuclein. The most recent leading hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Lindquist and co-workers reported that plasma membrane is a major nucleation site for αsyn aggregation, which sustains our results showing that fewer toxic conditions are associated with decreased presence of αsyn–GFP membranal inclusions. It is also described that the deposition of aggregated αsyn in perinuclear inclusions modulates its toxicity [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lindquist and co-workers reported that plasma membrane is a major nucleation site for αsyn aggregation, which sustains our results showing that fewer toxic conditions are associated with decreased presence of αsyn–GFP membranal inclusions. It is also described that the deposition of aggregated αsyn in perinuclear inclusions modulates its toxicity [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of aSyn detected in oligodendroglial GCIs still remains enigmatic and there are controversial studies in the literature suggesting either the internalization of neuronally-secreted aSyn by oligodendrocytes or an enhanced expression and decreased degradation of oligodendroglial aSyn [ 655 , 656 , 657 , 658 , 659 , 660 , 661 ]. The release of aSyn by neuronal cells, partially bound on vesicles or exosomes is well-documented [ 365 , 366 , 380 , 662 , 663 ] and some studies propose that oligodendrocytes can take-up the neuronally-derived aSyn via dynamin GTPase-, clathrin- and dynasore-dependent mechanisms [ 658 , 664 , 665 , 666 ].…”
Section: Glia In the Cns: Scavengers Of Extracellular Asynmentioning
confidence: 99%
“…Furthermore, phosphorylated α-syn was observed in GCIs ( Fujiwara et al, 2002 ). Abnormal accumulation of α-syn occurs with the demyelination and brain atrophy associated with neurodegeneration ( Yoon et al, 2020 ). We already mentioned that MSA is caused by aggregated α-syn in GCIs.…”
Section: α-Synuclein-induced Pathological Changes In Glial Cellsmentioning
confidence: 99%